Knowledge Management for Educational Innovation IFIP WG 3.7 7th Conference on Information Technology in Educational Management (ITEM), Hamamatsu, Japan, July 23-26, 2006 - Tatnall, Arthur.; Tatnall, Arthur.; Okamoto, Toshio.; Okamoto, Toshio.; Visscher, Adrie.; Visscher, Adrie. (IFIP Advances in Information and Communication Technology,, 2007)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of referred international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com. For more information about IFIP, please visit www.ifip.org.